Effects of intensification of the Indian Summer Monsoon on northern Andaman Sea sediments during the past 700 years. (May 2017) - Ota, Yuki; Kawahata, Hodaka; Murayama, Masafumi; Inoue, Mayuri; Yokoyama, Yusuke; Miyairi, Yosuke; Aung, Thura; Hossain, H. M. Zakir; Suzuki, Atsushi; Kitamura, Akihisa; Moe, Kyaw Thu
ABSTRACT: Recent studies have revealed an intensification of the Indian Summer Monsoon (ISM) over the past 700 years, but its influence on the sediments in the northern Andaman Sea is unclear. To examine this influence, we used radiocarbon‐dated sediment core StMY6, acquired 100 km offshore in the northern Andaman Sea from the Ayeyarwady River mouth, and obtained a 700‐year‐long record of the grain‐size distribution and geochemistry of the sedimentary sequence. The ISM influences precipitation surrounding the Ayeyarwady River, and thus the river water and sediment discharges to the northern Andaman Sea near the river mouth in the Ayeyarwady River and the weathering intensity in the river catchment. Based on the system, we propose that higher sedimentation rates and larger modal grain size (the most abundant size in the grain‐size distribution of sediments) and lower carbonate concentrations after about AD 1600 can be attributed to higher ISM intensity. Profiles of total organic carbon (TOC) content and carbon/nitrogen (C/N) ratios, however, did not show any trends after about AD 1600, which suggests that the ISM has had little influence on these proxies at this site.